The effects of eccentric versus concentric resistance training on muscle strength and mass in healthy adults: a systematic review with meta-analysis - Roig, M.; O`Brien, K.; Kirk, G.; Murray, R.; McKinnon, P.; Shadgan, B.; Reid, W. D. (British Journal of Sports Medicine, 2009)
The aim of this systematic review was to determine if eccentric exercise is superior to concentric exercise in stimulating gains in muscle strength and mass. Metaanalyses were performed for comparisons between eccentric and concentric training as means to improve muscle strength and mass. In order to determine the importance of different parameters of training, subgroup analyses of intensity of exercise, velocity of movement and mode of contraction were also performed. Twenty randomised controlled trials studies met the inclusion criteria. Meta-analyses showed that when eccentric exercise was performed at higher intensities compared with concentric training, total strength and eccentric strength increased more significantly. However, compared with concentric training, strength gains after eccentric training appeared more specific in terms of velocity and mode of contraction. Eccentric training performed at high intensities was shown to be more effective in promoting increases in muscle mass measured as muscle girth. In addition, eccentric training also showed a trend towards increased muscle cross-sectional area measured with magnetic resonance imaging or computerised tomography. Subgroup analyses suggest that the superiority of eccentric training to increase muscle strength and mass appears to be related to the higher loads developed during eccentric contractions. The specialised neural pattern of eccentric actions possibly explains the high specificity of strength gains after eccentric training. Further research is required to investigate the underlying mechanisms of this specificity and its functional significance in terms of transferability of strength gains to more complex human movements.